2021
DOI: 10.1080/0309877x.2021.1912306
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness, self-compassion, resiliency and wellbeing in higher education: a recipe to increase academic performance

Abstract: Universities are facing a difficult challenge in supporting good mental health whilst striving to enhance academic performance. The present study aimed to specifically investigate the relationship between attitudinal and personality constructs that are associated with wellbeing and to explore their association with student academic outcomes. Two-hundred and six undergraduate students were recruited and were given questionnaires measuring mindfulness, self-compassion, resiliency, procrastination, consideration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 56 publications
0
14
0
1
Order By: Relevance
“…The data showed that many staff felt bullied, while others were still dealing with the trauma experienced during the 2015-2017 student protests and suffered from depression and anxiety as a result. This decrease in emotional wellbeing resonates with the alarming global trend, which shows that staff in higher education, worldwide, are experiencing concerns regarding their overall wellbeing and, therefore, the university needs to provide meaningful and effective wellness programmes for staff (Egan, 2021). Transparency in recruitment, development and advancement processes were also highlighted as a concern.…”
Section: Example Survey Findingsmentioning
confidence: 97%
“…The data showed that many staff felt bullied, while others were still dealing with the trauma experienced during the 2015-2017 student protests and suffered from depression and anxiety as a result. This decrease in emotional wellbeing resonates with the alarming global trend, which shows that staff in higher education, worldwide, are experiencing concerns regarding their overall wellbeing and, therefore, the university needs to provide meaningful and effective wellness programmes for staff (Egan, 2021). Transparency in recruitment, development and advancement processes were also highlighted as a concern.…”
Section: Example Survey Findingsmentioning
confidence: 97%
“…Selain itu disebutkan bahwa salah satu bentuk manfaat lainya adalah peningkatan motivasi belajar. Dalam penelitian Egan H. et al (2021) menjelaskan bahwa self compassion merupakan bagian dari mindfulness dan dapat membantu siswa untuk menjadi mereka dapat menolong siswa untuk menjadi lebih kuat, dan pada dasarnya, terus berusaha untuk belajar dan meningkatkan diri selama di sekolah. Hal ini menjelaskan bahwa mindfulness memiliki peran dalam meningkatkan motivasi belajar sehingga dapat meningkatkan prestasi belajar siswa.…”
Section: B Pembahasanunclassified
“…The field of psychology has a clear foundation for providing individual counselling both within and beyond the university sector. However, there is consensus that a broad mental health approach is required that addresses systemic and individual prevention of problems by removing structural barriers, alongside programs that support flourishing, resilience, and agency [15,16]. As outlined in the 2020 Australian University Mental Health Framework [17], an overarching focus on collaborating with students in the co-design and planning of inclusive mental health services, involving peer-support initiatives and emphasising the student experience to support healthy learning environments is needed.…”
Section: Programsmentioning
confidence: 99%